ASSESSING THE ATTITUDES OF FOREST INDUSTRY COMPANIES OPERATING IN NORTH-WESTERN RUSSIA TOWARDS FOREST CERTIFICATION - Trishkin, Maxim; Karjalainen, Timo; Lopatin, Eugene (European Scientific Journal, ESJ, 2013)
This study explores the attitudes associated with forest certification among forest industry companies. The interviews were carried out in form of structured questionnaire from September to December 2011, with 35 forest industry companies operating in North-Western Russia that supply primary and value-added wood products, where 40% represented non-certified companies and 60% had a valid certificate. The interviewed companies represented 70% of market share in terms of wood consumption in North-Western part of Russia. Thus, development of certification in individual companies was initiated by general market demand; however, representatives of certified companies also emphasized the importance of internal corporate policy. Both groups of respondents identified market demand as a main driving force influencing on the development of forest certification. Insuring the legality of wood origin, company’s image and competitiveness of wood products were recognized as the most important benefits associated with forest certification. Absence of mandatory requirements from authorities and customers appeared to be the largest obstacle among both groups of respondents, in addition to that the representative of non-certified companies pointed out economic inaccessibility and low level of preparedness of management as of high importance, which is mainly associated with absence of quality management system. The results of the study indicated a general positive attitude; however it was noticed that respondents have gaps in understanding the principles and limited awareness with regards to forest certification, especially among non-certified forest industry companies.